The Attribution of Mental Health Problems to Jinn: An Explorative Study in a Transcultural Psychiatric Outpatient Clinic - Lim, Anastasia; Hoek, Hans W.; Ghane, Samrad; Deen, Mathijs; Blom, Jan Dirk (Frontiers in Psychiatry, 2018)
Background Among Muslim patients, a common cultural concept of distress is the notion that jinn may be the cause of mental health problems, especially in the presence of hallucinations. Objective This study examines the frequency with which this attribution style is manifest in a specific psychiatric outpatient population with a Muslim background. Methods Of all patients registered at an outpatient clinic specialized in transcultural psychiatry, data were collected on folk belief, religion, hallucinations (if present), and medical diagnosis. Through a search in the electronic medical files, the notes made during the first contact and first psychiatric examination were screened for the keywords “evil eye,” “magic,” “voodoo,” and “jinn.” In addition, new eligible cases were accepted. Results From all 551 patients thus screened, 118 were eligible for participation. Of these, 49 (41.5%) were interviewed using a semi-structured questionnaire. Among them, 21 (43%) were positive that their psychiatric symptoms were caused by jinn, whereas 13 (27%) thought not, and 15 (31%) were in doubt. No less than 87.2% had experienced hallucinations during their lives. Among the relatively large proportion of eligible patients who did not participate (58.5%), many expressed a fear for stigmatization or metaphysical repercussions if they spoke about jinn. Conclusion The phenomenon of attributing mental health symptoms to jinn was much more common in this population of Muslim patients than previously assumed. This underscores the need for proper knowledge of Muslim explanatory models of disease and for the use of culturally sensitive interviewing techniques in this population.